2017
DOI: 10.1111/1467-9817.12107
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effectiveness of a computer‐assisted reading intervention

Abstract: Background A cost‐effective method to address reading delays is to use computer‐assisted learning, but these techniques are not always effective. Methods We evaluated a commercially available computer system that uses visual mnemonics, in a randomised controlled trial with 78 English‐speaking children (mean age 7 years) who their schools identified as needing reading support. School‐based individual tutorials usually took place 2–3 times/week. Only the experimental group received the intervention in the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 62 publications
4
25
2
Order By: Relevance
“…We focused on vowels because, in English, the highly inconsistent graphemephoneme mapping is a major hurdle for struggling readers. In a landscape of digital tools that provide instant corrections at the whole word level, the phonemic cue annotation in this study is one of a only a few learning aids that provides an element of instruction (at the phoneme level) to support generalizable skill [31,33,43,50]. Instead of being given the answer at the first sign of struggle, the child can utilize the phonemic cue to learn part of the word, yet still needs to exercise the building blocks of literacy to get the answer.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…We focused on vowels because, in English, the highly inconsistent graphemephoneme mapping is a major hurdle for struggling readers. In a landscape of digital tools that provide instant corrections at the whole word level, the phonemic cue annotation in this study is one of a only a few learning aids that provides an element of instruction (at the phoneme level) to support generalizable skill [31,33,43,50]. Instead of being given the answer at the first sign of struggle, the child can utilize the phonemic cue to learn part of the word, yet still needs to exercise the building blocks of literacy to get the answer.…”
Section: Plos Onementioning
confidence: 99%
“…One promising avenue for such technology has been the use of embedded support features such as visual images to facilitate learning sound-symbol correspondence. For example, Trainertext, a program in the United Kingdom which provides visual mnemonics above each phoneme in a given text, saw significant improvement after 10 months of exposure and at-home practice [31]. By providing a visual scaffold, the authors concluded that readers could leverage a phonics-based text adaptation to improve their decoding skill.…”
Section: Introductionmentioning
confidence: 99%
“…These studies address some of © 2020 NASEN the methodological weaknesses of earlier studies and would therefore have met the criteria for inclusion in reviews such as those conducted earlier by Slavin et al (2011) and Cheung and Slavin (2013). The CARI used by Messer and Nash (2018) in their London research provided opportunities for 78 children with reading delays to develop their phonological awareness and decoding skills. Their randomised controlled trial found the CARI to be effective in these areas and children also showed improvements in spelling.…”
Section: Caris and Learningmentioning
confidence: 99%
“…() and Cheung and Slavin (). The CARI used by Messer and Nash () in their London research provided opportunities for 78 children with reading delays to develop their phonological awareness and decoding skills. Their randomised controlled trial found the CARI to be effective in these areas and children also showed improvements in spelling.…”
Section: Introductionmentioning
confidence: 99%
“…While these students improved in reading fluency by approximately one grade level, this was equivalent to the improvement of children who logged in for an average of only 25 h. The 4th-graders in the highuse group might have hit a roadblock that hindered them from making progress, despite spending additional time on the program. Feeling stuck with a program might have led to student frustrations, which, in turn, could affect the teachers' view of the program (Messer and Nash, 2018;cf., Fan and Williams, 2018).…”
Section: Weaknesses Of the Mvrcmentioning
confidence: 99%